2017
DOI: 10.1186/s40104-017-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of in ovo injection with the prebiotic DiNovo® on the development of histomorphological parameters of the duodenum, body mass and productivity in large-scale poultry production conditions

Abstract: BackgroundAmong various feed additives currently used in poultry nutrition, an important role is played by bioactive substances, including prebiotics. The beneficial effect of these bioactive substances on the gastrointestinal tract and immune system give rise to improvements in broiler health and performance nutrition, thus increasing the productivity of these birds. An innovative method for introducing bioactive substances into chickens is the in ovo injection into eggs intended for hatching. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…Awad et al (), Awad et al () tested synbiotic and probiotic action in broiler chickens, obtaining significant enhancement of villus height and height/crypt ratio in the ileum and duodenum when compared to the control group, which is a significant achievement for broiler producers since short villi and deep crypts may lead to poor nutrient absorption, increased secretion and low performance. As expected, bioactive substances improved the structure of all three segments of the small intestine of broiler chickens, as in previous work performed by Sobolewska et al () and Bogucka et al ().…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Awad et al (), Awad et al () tested synbiotic and probiotic action in broiler chickens, obtaining significant enhancement of villus height and height/crypt ratio in the ileum and duodenum when compared to the control group, which is a significant achievement for broiler producers since short villi and deep crypts may lead to poor nutrient absorption, increased secretion and low performance. As expected, bioactive substances improved the structure of all three segments of the small intestine of broiler chickens, as in previous work performed by Sobolewska et al () and Bogucka et al ().…”
Section: Resultssupporting
confidence: 89%
“…On to the control group, which is a significant achievement for broiler producers since short villi and deep crypts may lead to poor nutrient absorption, increased secretion and low performance. As expected, bioactive substances improved the structure of all three segments of the small intestine of broiler chickens, as in previous work performed by Sobolewska et al (2017) and Bogucka et al (2017).…”
Section: Re Sults and Discussionsupporting
confidence: 89%
“…Intra‐amniotic administration of synbiotics had a positive impact on feed conversion ratio at 22–42 days of age and 0–42 days, as well as on the proliferating cell nuclear antigen, villus height, and goblet and positive cell counts in broiler chickens . Prebiotics administered in ovo also resulted in a positive impact on the gut health of chicks and improving their overall development . Adult‐derived microbiota administered via the in ovo route has been shown to influence the development of microbiota in chickens along with the reduction in the prevalence of pathogenic bacteria .…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%
“…113 Prebiotics administered in ovo also resulted in a positive impact on the gut health of chicks and improving their overall development. 114 Adult-derived microbiota administered via the in ovo route has been shown to influence the development of microbiota in chickens along with the reduction in the prevalence of pathogenic bacteria. 115 In ovo administration of Flora Max ® -B11 indicated a positive effect on hatchability of chickens, gain in BW, and fall in a count of Salmonella enteritidis.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…To date, only few in ovo studies reported the application of prebiotics in ovo [6,7]. Regarding the performance objectives (body weight, feed intake and feed conversion ratio, FCR), the results for different prebiotics or synbiotics are found to be inconsistent, but consequently supporting the stimulating effect on gut development [8], immune gene expression [9], and improved resistance [10].…”
Section: Introductionmentioning
confidence: 99%